Konsep Kebahagiaan Perspektif Filsuf Muslim (Al-Farabi dan Al-Kindi) - Maulana Hakim; Radea Yuli A Hambali (UIN Sunan Gunung Djati Bandung, 2023)
The main objective of this study is to discuss the concept of happiness from the perspective of Muslim philosophers namely Al-Farabi and Al-Kindi. This research used a qualitative method through literature study. The results and discussion of this research are that happiness has become an eternal concept that will always change, the concept of happiness is not a taboo in the world of philosophy, so it has gone through various dynamics of its development. Al-Farabi and Al-Kindi have the same background but they have different views on the concept of happiness. Al-Farabi argues that happiness is the good that is desired for the good itself. Al-Kindi argues that the concept of happiness is the primacy of rational thinking, which means imitating God's actions. The conclusion of this study is that to achieve happiness one must understand with certainty from theoretical matters to achieving commendable habits.